1978
DOI: 10.1007/bf00344913
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen budget of a shortgrass prairie ecosystem

Abstract: A N budget is presented for a shortgrass prairie ecosystem. The grassland was ungrazed by domestic herbivores. The quantities of N in various plant, animal, microorganism, and soil components of the ecosystem are estimated for the date when aboveground living biomass was at its maximum for the growing season of 1973. Annual transfers of N between the various compartments were also estimated.Of the total N, 99.5% was in organic forms. The relatively inert heteropolycondensate fraction of the organic matter in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 19 publications
4
26
0
2
Order By: Relevance
“…Much attention has been devoted to the biogeochemical cycles of North American grasslands (e.g. Woodmansee et al 1978, Risser & Patton 1982, Schimel et al 1985b, including studies of nitrogen cycling on prairie dog (Cynomys Zudovicianus) colonies grazed by bison (Bison bison) in mixed-grass steppe (Holland & Detling 1990, Holland et al 1992. However, little is known about nutrient dynamics of temperate grassland ecosystems supporting large herds of free-roaming ungulates.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been devoted to the biogeochemical cycles of North American grasslands (e.g. Woodmansee et al 1978, Risser & Patton 1982, Schimel et al 1985b, including studies of nitrogen cycling on prairie dog (Cynomys Zudovicianus) colonies grazed by bison (Bison bison) in mixed-grass steppe (Holland & Detling 1990, Holland et al 1992. However, little is known about nutrient dynamics of temperate grassland ecosystems supporting large herds of free-roaming ungulates.…”
Section: Introductionmentioning
confidence: 99%
“…A second objective was to determine whether growth under elevated CO 2 would alter forage digestibility of codominant species, as it had in the tallgrass prairie where lower forage N concentration was cited as a contributive factor (Owensby et al 1996a). Since N is cycled tightly in the shortgrass steppe, with much of it tied up in microbial biomass (Woodmansee et al 1978), we hypothesized that forage quality would decline in the shortgrass steppe under elevated CO 2 due to the inability of those soils to provide additional N to keep pace with CO 2 -induced growth responses , and would be reflected in reductions in in vitro dry-matter digestibility for all species. We also hypothesized that the decline in forage quality would be similar across species, based on the assumption of similar species production responses to CO 2 enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the content of inorganic N in wetland soil is much lower, and it is often the most limited nutrient which directly affects the productivity of wetland ecosystem (Mistch and Gosselin, 2000). At present, the studies related to N cycling in wetland were widely reported by researches (Woodmansee et al, 1978;Hayes, 1985;Yoneyamad et al, 1993;Middelburg and Joop, 1998), some researchers also adopted 15 N technique to study the movement, transformation and fate of N (McKinney et al, 2001;Nordbakken et al, 2003;Ulrike et al, 2004). In general, these researches Project supported by the Knowledge Innovation Foundation of Chinese Academy of Sciences (KZCX2-YW-309, KZCX3-SW-332) and the National Natural Science Foundation of China (No.…”
Section: Introductionmentioning
confidence: 99%